Understanding the Reactivity of Acyl Anion Equivalents: The Epoxide Ring Opening Case - Eger, Wilhelm A.; Grange, Rebecca L.; Schill, Heiko; Goumont, Regis; Clark, Timothy; Williams, Craig M. (European Journal of Organic Chemistry, 2011)
Acyl anion equivalents (umpolung) are the practitioner's first choice en route to 1,3-hydroxy keto compounds from epoxides. Why? This investigation evaluates computationally and experimentally the reactivity of a near comprehensive range of acyl anion equivalents using epoxide ring opening as a test vehicle. Reactivity understanding, reactivity order, surprise failures in performance, along with unprecedented, but far from superior, reactivity of TosMIC is presented for the first time.
Keywords: Umpolung; Epoxides; Acyl anion equivalent; Carbonyl equivalent